The Role of Social Media in Constructing the Destination Image of Moslem Friendly Tourism in Indonesia - Maysara, Djamalova; Rahmat, Shartono; Shaik Azahar, Shaik Hussain; Lilik Edi, Saputro; Nina, Mistriani; Ahmad Rizaldi, Aspri (EDP Sciences, 2025)
This study examines the pivotal role of social media in shaping and constructing the destination image of Moslem Friendly Tourism in Indonesia. Using a qualitative approach, this research analyzes data from interviews, document reviews, and content analyses of user-generated content across major digital platforms. The findings highlight that social media functions not only as a promotional tool but also as a cultural space for constructing authentic narratives about Moslem Friendly Tourism. The study contributes to the growing discourse on digital destination branding by emphasizing the importance of balancing promotional efforts with cultural authenticity. The results suggest that user-generated content and influencer advocacy significantly affect travelers’ perceptions, enhancing trust and credibility. This paper provides theoretical and practical insights for stakeholders aiming to strengthen Indonesia’s position in the global halal tourism market while preserving its cultural integrity.